PERLINDUNGAN KONSUMEN DALAM E-COMMERCE BERDASARKAN UNDANG-UNDANG NO. 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NO. 11 TAHUN 2008 DAN TRANSAKSI ELEKTRONIK, DAN UNDANG-UNDANG NO.8 TAHUN 1999 - Amelia, Risky; Wahyuni, Nurul; Angelica Suwanto, Bunga; Efriza, Selviana (Teknik Mesin ,Universitas Pamulang Serang, 2024)
Pamulang University carries out community service as part of the Tri Dharma of Higher Education. This includes assisting people in realizing their potential and achieving fair and equitable knowledge and skills without expecting any form of reward. The first step is to identify social problems that need to be addressed immediately or whose potential has not been exploited. Research or re-examination of findings through application, development, and dissemination of information can be used to carry out these efforts. Various advances in various sectors, especially information technology, have occurred along with the current development of information technology. Of course, online buying and selling is one of them. Because transaction activities are of course carried out via online media, we must be aware of the legal implications, especially to ensure the upholding of the rights and obligations of each party. Customers often experience a sense of insecurity when carrying out transaction procedures. Furthermore, the validity of transaction procedures is in accordance with article 1458 of the Civil Code (KUHPer) as a guideline in transaction agreements. Because these activities often give rise to legal problems, one of which is fraud committed by internet business people who carry out buying and selling. Given this, community outreach initiatives are needed to educate the public about the risks associated with this problem. Keywords : Buying and Selling, Transactions, Online